Christmas Break: Predictive Value of Holiday Avian Wishbone Traditions Among Frontline Healthcare Workers in a Prospective Trial - Loevinsohn G; Wizda CN; Glynn TR; Erickson TB; Chai PR (Risk Management and Healthcare Policy)
Gideon Loevinsohn,1 Caitlin N Wizda,1 Tiffany R Glynn,1,2 Timothy B Erickson,1,3 Peter R Chai1,4,5 1Department of Emergency Medicine, Brigham and Women’s Hospital, Boston, MA, USA; 2Department of Psychiatry, Massachusetts General Hospital, Boston, MA, USA; 3Harvard Humanitarian Institute, Cambridge, MA, USA; 4Department of Psychosocial and Palliative Care, Dana Farber Cancer Institute, Boston, MA, USA; 5The Fenway Institute, Fenway Health, Boston, MA, USACorrespondence: Peter R Chai, Department of Emergency Medicine, Brigham and Women’s Hospital, 75 Francis Street, Boston, MA, USA, Tel +1 617-732-5640, Email pchai@bwh.harvard.eduObjective: To assess the impact of winning a wishbone contest on the likelihood of subsequent goal attainment.Design: Prospective cohort study.Setting: A large urban academic emergency department in the United States.Participants: 40 frontline emergency department clinicians including supervising and resident physicians and physician assistants. Participants were enrolled between December 8, 2023 and January 10, 2024 and followed for three months.Main Outcome Measures: The primary outcomes were feasibility of performing wishbone contests in the emergency department and attainment of a pre-specified wish by the end of the three-month follow-up period.Results: Forty participants who met eligibility criteria were enrolled in the study and 37 completed follow-up at three months. Half identified as female and professional roles (resident physician, attending physician and physician assistant) were equally distributed. Overall, 38% of wishes were realized at three month follow-up. There was no association between winning the wishbone competition and realizing the wish. Participants who perceived a greater degree of control over the outcome of their wish were more likely to have their wish realized (RR1.2, 95% CI 1.05– 1.37).Conclusion: Frontline healthcare workers will engage in luckiness-boosting wishbone contests even in a busy emergency department environment. In our study, there was no association between winning the wishbone competition and goal or wish achievement. Participants who reported and perceived a greater degree of control over the outcome of their wish, however, were more likely to have their wish realized. Holiday cheer and wishful thinking traditions may indicate the feasibility of future work in extending positive thinking among frontline healthcare workers.Keywords: positive thinking, Turkey, wishbone, affect, emergency medicine, training, luck, cognitive training